2014
DOI: 10.1007/s13311-014-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging the Epileptogenic Process

Abstract: Epilepsy is one of the most common chronic neurological conditions worldwide. Anti-epileptic drugs (AEDs) can suppress seizures, but do not affect the underlying epileptic state, and many epilepsy patients are unable to attain seizure control with AEDs. To cure or prevent epilepsy, disease-modifying interventions that inhibit or reverse the disease process of epileptogenesis must be developed. A major limitation in the development and implementation of such an intervention is the current poor understanding, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 116 publications
0
32
0
Order By: Relevance
“…As indicated by a significant injury  treatment interaction and post hoc analysis (F 1,19 ¼ 5.104, p < 0.05; 3mTBI þ VEH < all other groups, p < 0.05; Fig. 4C), the 3mTBI þ VEH group had a significant reduction in mean FA in the corpus callosum compared to every other group, suggesting axonal injury (Shultz et al, 2014a). Tractography analysis further revealed that 3mTBI þ VEH rats had significantly fewer tracts (injury  treatment interaction: F 1,19 ¼ 5.104, p < 0.05; 3mTBI þ VEH < 3mTBI þ SS < both SHAM groups, p < 0.05; Fig.…”
Section: Sodium Selenate Treatment Attenuates Brain Damage Induced Bymentioning
confidence: 84%
See 1 more Smart Citation
“…As indicated by a significant injury  treatment interaction and post hoc analysis (F 1,19 ¼ 5.104, p < 0.05; 3mTBI þ VEH < all other groups, p < 0.05; Fig. 4C), the 3mTBI þ VEH group had a significant reduction in mean FA in the corpus callosum compared to every other group, suggesting axonal injury (Shultz et al, 2014a). Tractography analysis further revealed that 3mTBI þ VEH rats had significantly fewer tracts (injury  treatment interaction: F 1,19 ¼ 5.104, p < 0.05; 3mTBI þ VEH < 3mTBI þ SS < both SHAM groups, p < 0.05; Fig.…”
Section: Sodium Selenate Treatment Attenuates Brain Damage Induced Bymentioning
confidence: 84%
“…All volumetric analysis procedures followed those previously described (Johnstone et al, 2015;Shultz et al, 2015bShultz et al, , 2015cShultz et al, , 2014aShultz et al, , 2014b. Volumes of eight manually drawn regions of interest (ROI), including the cortex, hippocampus, corpus callosum, and lateral ventricles from both hemispheres, were quantified using the T 2 -weighted MRI images (FSL, Analysis Group, Oxford, UK).…”
Section: Mri Analysismentioning
confidence: 99%
“…As seizure‐related brain atrophy, as well as lesions such as hemimegalencephaly, may alter brain weight in either direction, we also analysed only SUDEP cases without macroscopic brain pathology, but there was only a trend for higher brain weights in females with SUDEP than in controls. One possible cause of the brain swelling is seizure‐mediated vasogenic oedema as sometimes noted on post‐ictal MRI and following status epilepticus [32,33]. As even mild degrees of brain swelling could potentially affect brainstem function through compression, improved recording of brain swelling in SUDEP PMs would be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of heterotopic neurons, abnormal myelination, edema, axonal injury and gliosis affect the diffusion properties traversing axonal tracts 10,11 . Figure 1 also shows tractography in the patient (top) and a normal age- and gender- matched control (bottom) obtained by seeding the white matter using DSI-Studio 12,13 .…”
Section: Resultsmentioning
confidence: 99%